Penguatan Identitas Merek dan Transformasi Digital Marketing pada UMKM Combro dan Misro Pak Idrus - Joni Heruwanto; Arifin Cahyono; Sabrina Rossa; Maesa Rizky Abdillah (JPPI: Jurnal Pengabdian Pelita Insani, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in economic development but often face challenges in marketing and brand strengthening. This study examines the MSME “Combro and Misro Pak Idrus,” which has limited digital marketing use, suboptimal packaging, and lacks structured customer management. Using a qualitative approach through observation and interviews, this research evaluates business conditions and designs strategies to enhance competitiveness. The findings show that rebranding, improved packaging, and optimized use of social media and digital platforms significantly increase visibility, brand image, and market reach. Therefore, digital marketing transformation is a strategic step to strengthen the sustainability of traditional culinary MSMEs.